A gadolinium-complex-based theranostic prodrug for in vivo tumour-targeted magnetic resonance imaging and therapy. Issue 31 (29th March 2019) - Yang, Zhaoxuan; Lin, Hongyu; Huang, Jiaqi; Li, Ao; Sun, Chengjie; Richmond, Jonathan; Gao, Jinhao
Abstract : A molecular theranostic prodrug for treatment of tumour and real-time monitoring via MRI in vivo was reported. Abstract : Here we report a target-specific theranostic prodrug (1a ) containing Gd–DOTA, biotin, and camptothecin (CPT) along with a disulfide self-immolative linker. This prodrug exhibits selective targeting towards tumour cells and tissues, stimuli-responsive controlled release, enhanced anticancer efficacy, and accurate diagnosis and real-time monitoring via contrast-enhanced magnetic resonance imaging (MRI).